On Lithuanian mathematical olympiads - Mačys, Juvencijus; Sušinskas, Jurgis (Lietuvos matematikos rinkinys, 2018)
Some problems of Lithuanian school mathematical olympiad 2018 and Vilnius University mathematical olympiad 2018 are considered. Different methods of solution are compared. Some useful common advices for solving mathematical problems are given.